Radiological impact assessment of natural radionuclides and heavy metal contamination in industrial tin-tailing processing effluent - Nursyamimi Diyana Rodzi,; Aznan Fazli Ismail,; Muhammad Abdullah Rahmat,; Eli Syafiqah Aziman,; Wan Mohd Razi Idris,; Tukimat Lihan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study investigates the radiological hazard and heavy metal contamination of water effluents from Malaysian tin-tailing processing plants. Samples were collected from retention ponds in seven separate tin tailing processing plants scattered throughout the state of Perak, Malaysia. Samples were analysed for radioactivity and heavy metal concentration using Gamma-ray Spectrometry System and Inductively Coupled Plasma-Mass Spectrometry, respectively. The analysis indicates that the concentration of Radium-226 (226Ra), Radium-228 (228Ra), and Potassium-40 (40K) in samples ranged from 2.4 - 34.9 Bq/l, 0.8 - 14.7 Bq/l, and 19.5 - 299.4 Bq/l, respectively. These levels surpassed the control limits (5 Bq/l and 10 Bq/l for 226Ra and 228Ra) set by the regulatory authority. The analysis of the heavy metal contamination showed that the concentration of Arsenic (As) and Lead (Pb) were higher than the Maximum Concentration Level (MCL) of 0.01 and 0.015 mg/L, respectively. Further evaluation of radiological impact showed that the average Annual Effective Doses (AED) by water ingestion and AED for external exposure are 1.43±0.67 mSv/y and 1.71±0.79 mSv/y, respectively. While for non-carcinogenic and carcinogenic risk assessments, the value of hazard index and lifetime cancer risk is 2.1×10-10 and 1.2×10-7, respectively. These research findings suggest that effective treatment of the effluent should be implemented before discharge into the drainage system to prevent the accumulation of radionuclides and heavy metals in the environment, which may pose a risk to public health.